2021
DOI: 10.1186/s12889-021-11705-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of medical male circumcision and sexually transmitted infections in a population-based study using targeted maximum likelihood estimation

Abstract: Background Epidemiological theory and many empirical studies support the hypothesis that there is a protective effect of male circumcision against some sexually transmitted infections (STIs). However, there is a paucity of randomized control trials (RCTs) to test this hypothesis in the South African population. Due to the infeasibility of conducting RCTs, estimating marginal or average treatment effects with observational data increases interest. Using targeted maximum likelihood estimation (TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…This research found a link between circumcision behavior in efforts to prevent the spread of STIs in this study, which is consistent with the theory that has been expressed and several previous studies, namely: circumcision behavior in heterosexual and homosexual groups prevents around 0.58 times greater than HIV and STI which are transmitted through sexual relations (Sharma et al, 2018). In South Africa, circumcision behavior can protect around 21.1% of Herpes Simplex Virus (HSV-2), and 31% prevent the occurrence of HIV and Hepatitis B in housewives compared to men (Amusa et al, 2021;Davis et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…This research found a link between circumcision behavior in efforts to prevent the spread of STIs in this study, which is consistent with the theory that has been expressed and several previous studies, namely: circumcision behavior in heterosexual and homosexual groups prevents around 0.58 times greater than HIV and STI which are transmitted through sexual relations (Sharma et al, 2018). In South Africa, circumcision behavior can protect around 21.1% of Herpes Simplex Virus (HSV-2), and 31% prevent the occurrence of HIV and Hepatitis B in housewives compared to men (Amusa et al, 2021;Davis et al, 2019).…”
Section: Discussionsupporting
confidence: 92%